2015
DOI: 10.3389/fnins.2015.00438
|View full text |Cite
|
Sign up to set email alerts
|

EEG Recorded from the Ear: Characterizing the Ear-EEG Method

Abstract: Highlights Auditory middle and late latency responses can be recorded reliably from ear-EEG.For sources close to the ear, ear-EEG has the same signal-to-noise-ratio as scalp.Ear-EEG is an excellent match for power spectrum-based analysis.A method for measuring electroencephalograms (EEG) from the outer ear, so-called ear-EEG, has recently been proposed. The method could potentially enable robust recording of EEG in natural environments. The objective of this study was to substantiate the ear-EEG method by usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
133
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 25 publications
10
133
1
1
Order By: Relevance
“…However, state of the art dry electrodes EEG systems still do not match electrodes with conductive gel applied in terms of data acquisition quality, and are less comfortable for the subjects (Oliveira et al, 2016). From an aesthetic point of view, recent studies have proposed in ear EEG sensors (Looney et al, 2012; Kidmose et al, 2013; Mikkelsen et al, 2015; Goverdovsky et al, 2016), around-the-ear electrodes grids (Debener et al, 2015; Bleichner et al, 2016; Mirkovic et al, 2016), or a baseball cap fitted with electrodes (Bleichner et al, 2015). Future developments in mobile brain imaging should therefore aim to increase the ease of use, discretion and comfort of the sensors while maximizing data quality in order to be successfully applicable in real-world settings.…”
Section: Current Challengesmentioning
confidence: 99%
“…However, state of the art dry electrodes EEG systems still do not match electrodes with conductive gel applied in terms of data acquisition quality, and are less comfortable for the subjects (Oliveira et al, 2016). From an aesthetic point of view, recent studies have proposed in ear EEG sensors (Looney et al, 2012; Kidmose et al, 2013; Mikkelsen et al, 2015; Goverdovsky et al, 2016), around-the-ear electrodes grids (Debener et al, 2015; Bleichner et al, 2016; Mirkovic et al, 2016), or a baseball cap fitted with electrodes (Bleichner et al, 2015). Future developments in mobile brain imaging should therefore aim to increase the ease of use, discretion and comfort of the sensors while maximizing data quality in order to be successfully applicable in real-world settings.…”
Section: Current Challengesmentioning
confidence: 99%
“…By directly comparing simultaneously acquired scalp-EEG and ear-EEG signals, several independent laboratories have shown that ear-EEG can capture brain signals that are closely related to those recorded with scalp-EEG (Mikkelsen et al, 2015; Mirkovic et al, 2015; Bleichner et al, 2016; Zibrandtsen et al, 2016). In contrast to the classical EEG cap, ear-EEG sensors can be worn comfortably and are not more noticeable than hearing-aids or (in-ear) headphones.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, significant progress has been made in the field of mobile electroencephalograms (EEGs) (De Vos, Gandras, & Debener, 2014;Debener, Minow, Emkes, Gandras, & de Vos, 2012), indicating that miniaturized EEG systems can be used outside the laboratory environment. An elegant solution to avoid placing electrodes on the head in locations where they are visible or difficult to apply, has been proposed in the form of a miniaturized EEG device placed in or around the ears, offering both a reliable and user-friendly alternative for full-scalp EEG (Mikkelsen, Kappel, Mandic, & Kidmose, 2015;Mikkelsen, Kidmose, & Hansen, 2017;Mikkelsen, Villadsen, Otto, & Kidmose, 2017;Pacharra, Debener, & Wascher, 2017). More specifically, several studies have reported progress towards using such ear-centered EEG devices for tracking the presence of different sleep stages (Looney, Goverdovsky, Rosenzwei, Morrell, & Mandic, 2016;Mikkelsen, Villadsen, et al, 2017;Stochholm, Mikkelsen, & Kidmose, 2016;Zibrandtsen, Kidmose, Otto, Ibsen, & Kjaer, 2016).…”
Section: Introductionmentioning
confidence: 99%